Boas práticas na gestão de resíduos sólidos urbanos: uma análise voltada a sustentabilidade - Flores, Carlos Eduardo Balestrin (2017)
One way to operationalize the concept of sustainability is by good practices, an instrument that can assist public managers in the process for the management of urban solid waste - USW. The ideology that researchers report on the population growth concentrated in urban centers and the lack of infrastructure as one of the main problems related to USW management is not new, generating a series of consequences for the environment. In the knowledge of the various environmental impacts caused by USW, the inclusion of good practices appears as alternatives to compose this system. The objective of this work is to identify good sustainability practices in the management of urban solid waste - USW applicable in the cities of Passo Fundo, Santa Maria and Porto Alegre, in the Rio Grande do Sul state, contributing to the implementation of municipal plans and the provisions of the National Policy of Solid Waste and the objectives of sustainable development. The methodology consisted of an exploratory bibliographical research along with a systematic review describing the current situation of USW in the cities of the study, the survey of good practices and success cases, the evaluation of good practices based on a known multicriteria technique Such as the Analytic Hierarchy Process -AHP with the aid of Expert Choice software, in the interpretation of data for hierarchy of criteria in the selection of a group of good practices through an evaluation matrix, as well as to evaluate the applicability through focus groups and the distribution of two scenarios in different dimensions and horizons for medium and large cities. The result consists of a group of twelve (12) good practices after analyzing the entire USW management system of the three (03) municipalities, expressing a favorable trend towards sustainability with the implementation of these practices, for the two described scenarios. However, this experience has shown that the implementation of a group of good practices should involve the participation of different social agents to encourage and provide the use of good practices throughout the USW management process, enabling sustainable alternatives, providing better life quality to society.